NONLINEAR BEHAVIOUR OF TWO-WHYTE STONE WALLS - Dinc-Sengonul, Burcu; Hothot, Yasin Murat; Doran, Bilge; Yuzer, Nabi; Ulukaya, Serhan; Oktay, Didem (INT CENTER NUMERICAL METHODS ENGINEERING, 2021)
Engineers work hard to convert the highly uncertain and nonlinear behavior of historic masonry structures into something that can be understood with mathematical certainty. Therefore, practical and also accurate structural analysis techniques are still needed for the preserve the historical monuments as a huge cultural heritage. In this context, determining the mechanical properties of historical walls under in-plane and out-of-plane lateral loadings is one of the most important aim. This study aims to investigate the three dimensional (3D) nonlinear behaviour of stone walls subjected to a combination of lateral and vertical loads using approprate constitutive numerical modeling. For this purpose, a simplified micro modeling approach has been proposed for the 3D nonlinear finite element analysis (NLFEA) of stone wall. The dry-stone masonry wall from the literature has been used in the verification step for the proposed model. After that, the new two-whyte stone wall has been constructed in accordance with the original material characteristics derived from the experimental studies and tested under shear compression. Finally, numerical results of NLFEA and experimental results of walls have been compared. It was observed that the numerical analysis results are well matched with the experimental ones.
Keywords: Historical Structure; Masonry; Stone Walls; Nonlinear Behaviour; MASONRY WALL; SHEAR; Architecture; Construction & Building Technology